The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.18632/aging.100745
|View full text |Cite
|
Sign up to set email alerts
|

Biological ageing and frailty markers in breast cancer patients

Abstract: Older cancer patients are a highly heterogeneous population in terms of global health and physiological reserves, and it is often difficult to determine the best treatment. Moreover, clinical tools currently used to assess global health require dedicated time and lack a standardized end score. Circulating markers of biological age and/or fitness could complement or partially substitute the existing screening tools. In this study we explored the relationship of potential ageing/frailty biomarkers with age and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 49 publications
2
54
0
1
Order By: Relevance
“…The LOFS is a GA summary score: it calculates a global GA end score that integrates 5 fundamental aspects determining a patient's fitness/frailty status (ie, his or her ability to autonomously perform activities of daily living [ADL and IADL], mental status [MMSE], nutritional status [MNA-SF], and comorbidities [CCI]) into a single semicontinuous score on a scale of 0 (severely frail) to 10 (fit) 41 (see Supporting Table 2). The LOFS is a GA summary score: it calculates a global GA end score that integrates 5 fundamental aspects determining a patient's fitness/frailty status (ie, his or her ability to autonomously perform activities of daily living [ADL and IADL], mental status [MMSE], nutritional status [MNA-SF], and comorbidities [CCI]) into a single semicontinuous score on a scale of 0 (severely frail) to 10 (fit) 41 (see Supporting Table 2).…”
Section: Ga Summariesmentioning
confidence: 99%
“…The LOFS is a GA summary score: it calculates a global GA end score that integrates 5 fundamental aspects determining a patient's fitness/frailty status (ie, his or her ability to autonomously perform activities of daily living [ADL and IADL], mental status [MMSE], nutritional status [MNA-SF], and comorbidities [CCI]) into a single semicontinuous score on a scale of 0 (severely frail) to 10 (fit) 41 (see Supporting Table 2). The LOFS is a GA summary score: it calculates a global GA end score that integrates 5 fundamental aspects determining a patient's fitness/frailty status (ie, his or her ability to autonomously perform activities of daily living [ADL and IADL], mental status [MMSE], nutritional status [MNA-SF], and comorbidities [CCI]) into a single semicontinuous score on a scale of 0 (severely frail) to 10 (fit) 41 (see Supporting Table 2).…”
Section: Ga Summariesmentioning
confidence: 99%
“…Another explanation could be the severity of inflammation. A study performed in breast cancer patients showed the IL-6 level significantly associated with frailty, but the CMV status was not reported (Brouwers et al 2015). In long-term care geriatric patients, higher baseline hs-CRP and IL-6 levels were associated with worse physical performance and gait speed at 12 months independent of age and comorbidity (Langmann et al 2017).…”
Section: And Frailtymentioning
confidence: 99%
“…Therefore, we evaluated the following biomarkers that have been associated with functional decline in the elderly: IL-6[28, 39, 55], D-dimers[56], albumin[57], IGF-1 & IGFBP3[58, 59], TNF-alpha[60] in plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy treatment has potential to increase senescent cells leading to an increase in inflammatory and DNA damage burden[34], which could interfere with muscle function [35, 36]. Elevated pro-inflammatory cytokines are correlated with fatigue in breast cancer survivors[37], patients with cancer in general [38] and frailty in breast cancer survivors [39]. …”
Section: Introductionmentioning
confidence: 99%